Digital Tourism Experiences for Tourist Site Revisit: An Empirical Review from Nepal - Dulal, Mandip; Aryal, Santosh (The Gaze: Journal of Tourism and Hospitality, 2024)
This study delves into the pivotal role of digital tourism experiences in influencing tourist site revisit behavior. It specifically hones in on the impact of technology-based service innovativeness, social value, and knowledge sharing through technology. These factors play a significant role in shaping tourists' intentions to return to their destinations. The study employs a quantitative research approach and a descriptive and correlational design and analyzes data collected from tourists engaged in both soft and hard adventure tourism activities. The findings underscore the strong correlations between technology-based service innovation, social value, and tourists' likelihood of revisiting destinations. The study reveals that both technology-based service innovation and social value positively influence experience sharing through technology and revisit intentions. Furthermore, experience sharing through technology emerges as a key mediator between technology-based service innovation and revisit behavior. The study's implications highlight the critical role of advanced technologies in enhancing tourism services, thereby boosting customer satisfaction, fostering loyalty, and creating a positive feedback loop through online content sharing. The study encourages tourism businesses to prioritize technological innovation, engage with tourists online, and tailor experiences to increase repeat visits and customer loyalty.